2013
DOI: 10.1016/j.jsmc.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Insomnia

Abstract: This paper summarizes recent epidemiological evidence on insomnia, including its prevalence, incidence, and risk factors, as well as its course and consequences. There is now substantial evidence that insomnia is a significant public health problem. It is a highly prevalent condition, both as a symptom and a syndrome, and is often a persistent condition over time. Its persistence is associated with increased risk for mental (major depression), physical (hypertension), and occupational health problems (disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(64 citation statements)
references
References 119 publications
4
57
0
3
Order By: Relevance
“…(16) With an estimated worldwide prevalence of 10%, insomnia is the most common sleep disorder. (15,17,18) Clinical diagnosis in accordance with the most recent diagnostic and statistical manual of mental disorders requires the patient to report difficulty initiating and/or maintaining sleep with subsequent daytime impairments greater than three nights per week and for at least three months.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…(16) With an estimated worldwide prevalence of 10%, insomnia is the most common sleep disorder. (15,17,18) Clinical diagnosis in accordance with the most recent diagnostic and statistical manual of mental disorders requires the patient to report difficulty initiating and/or maintaining sleep with subsequent daytime impairments greater than three nights per week and for at least three months.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…With regards to criminogenic factors, three studies examined unconvicted and sentenced prisoners, finding that insomnia tended to be more common in the former [22, 43,44]. Overall, insomnia symptoms prevalence was higher in a prison population than in the general population (30%e 36%) [8] with the exception of just two studies (10.9% and around 20%) [40,51]. The former study identified this figure based on whether the prisoner had been prescribed hypnotic medication only and not by prisoner self-report of insomnia symptoms.…”
Section: Theme 1: the Varied Prevalence Of Insomniamentioning
confidence: 99%
“…This wide prevalence range reflects the differing definitions of insomnia and the variety of assessment tools adopted by different studies [8]. In terms of agreed definitions of insomnia, all three commonly used sleep classification manuals accept that the main symptoms of insomnia are a persistent problem initiating or maintaining sleep; experiencing early morning awakenings; and/or non-restorative sleep [9e11].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia, as a syndrome or symptom, is a widespread and persistent problem (1). People with insomnia experience a wide range of problems such as fatigue, irritability, difficulties in memorization and concentration, impairment of daily functions, and reduced quality of life (2).…”
Section: Introductionmentioning
confidence: 99%